Exotic properties of superfluid He - Volovik G.E (World Scientific, 1992)
This book discusses the unique properties of superfluid phases 3He, the condensed matter with the outmost broken symmetry, which combine in a surprising way the properties of ordered magnets, liquid crystals and superfluids. The complicated vacuum state of these phases with a large number of fermionic and bosonic quasiparticles and topological objects remains the vacuum in modern quantum field theories. Some of the objects and physical phenomena in 3He have strong analogy with the neutrino, w-bosons, weak interactions, gravity, chiral anomaly, quantum Hall effect and fractional statistics. As an example of topological objects, the quantized vortices in 3He phases are discussed in detail, including singular and continuous vortices, half-quantum vortices, broken symmetry in the vortex core and phase transitions between the vortex states with different symmetry and topology.